The Activity of Plant Crude Extracts against Schistosoma mansoni - Hirut Basha; Hassen Mamo (Journal of Parasitology Research)
Background. Schistosoma mansoni remains a significant health problem in low-income countries. Praziquantel (PZQ) is the only drug available to treat schistosomiasis, and PZQ resistance is a potential threat towards control of the disease although PZQ is currently effective against all species of schistosomes. Moreover, PZQ is less efficacious against larval stages. In response to these challenges, multiple in vivo/in vitro studies evaluated the anti-S. mansoni activity of crude plant extracts in a bid for novel drug(s). However, these studies appear fragmented and patchy. This systematic review explored the extent of such studies in the past 11 years (2010-2020). Methods. A systematic web search analysis and review of the literature on crude plant extracts tested against S. mansoni was done. Data from 17 articles meeting eligibility criteria were extracted and analyzed. Forty-three plant species have been tested by the 17 studies. The leaves, barks, stems, flowers, rhizomes, and roots of the plants as well as the whole plant part were used for the experiments. Conclusion. Nearly all of the plants significantly reduced schistosome egg output, killed adult worms, and improved liver histology and function. Further studies are required to assess the therapeutic potential of more promising plant species.